ADOPTION OF THE JAMSOSTEK MOBILE (JMO) APPLICATION IN BPJS KETENAGAKERJAAN LHOKSEUMAWE BRANCH - Hasya Tillah; Yuna Regita Cahyani; Chilvi Alnura; Rozatun Nufus; Yusmika Indah; Halimatus Sa’diyah; Rahmi Raihan (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2023)
This study examines the implementation of the Jamsostek Mobile Application (JMO) as a digital innovation by BPJS Ketenagakerjaan in delivering services to participants, particularly at the Lhokseumawe Branch Office. The purpose of this research is to analyze the extent of JMO implementation, the features utilized, and the challenges encountered. The research employs a descriptive qualitative method through observation and interviews. The findings show that the JMO application has provided significant benefits such as time efficiency, 24-hour service access, transparency of balance and claims information, and reduced manual administrative burdens. Nevertheless, challenges remain, including limited digital literacy, restricted internet access, and technical issues within the application. User data also indicate fluctuations, these trends highlight the inconsistency of usage despite continuous feature development. Therefore, sustainable socialization, digital literacy improvement (especially for informal workers and the elderly), system stability enhancement, and collaboration with labor communities and digital villages are needed to optimize JMO adoption and strengthen public trust in BPJS Ketenagakerjaan.